Assessing pressure drivers on the benthic ecosystem in the coastal zone of Western Messinia, Greece. (5th September 2022) - Bray, Laura; Faulwetter, Sarah; Kaberi, Helen; Karageorgis, Aristomenis P.; Kastanidi, Erasmia; Katsiaras, Nikolaos; Pavlidou, Alexandra; Providakis, Nikolaos; Sigala, Kaliopi; Voutsinas, Emanuela; Zeri, Christina; Reizopoulou, Sofia
Abstract: The Messinia region, located in the South – West of the Peloponnese, Greece, is an ecologically valuable area comprising of several important coastal habitats (including coastal lagoons, seagrass meadows, and Mediterranean rhodolith beds) eliciting its inclusion in the Natura 2000 network. Land-based anthropogenic pressures are likely to influence the ecological status of this coastal zone. Here we identify those regional pressures and use physico-chemical elements of the ecosystem, and the status of the macrofauna communities to assess the level of environmental degradation in the coastal and lagoon water bodies. High organic load from the catchment area, geomorphological and hydrological features of the water bodies are the major drivers affecting the ecological quality of the region. The lagoon is severely degraded due to both a high nutrient input from the surrounding river basin (likely due to agricultural run-off), and a relatively low level of connectivity with the marine environment (due to alterations in the regional hydrology). In contrast, the coastal zone is classified as being at a high or good ecological status and seems scarcely impacted by anthropogenic pressures. The macrobenthic communities reflect how vulnerable the lagoon is to multiple stressors (and in particular agricultural practices), and highlight the necessity of defining and implementing holistic, river-basin based management plans for the Gialova lagoon, and the surrounding coastal area of Messinia . Graphical abstract: Image 1 Highlights: Main pressures for Western Messinia coastal zone are agriculture and hydrological changes. Anthropogenic pressures impact lagoon waterbody more than coastal zone. Macrobenthos communities reflect differences in levels of anthropogenic pressures.